2013
DOI: 10.1002/2013jc008963
|View full text |Cite
|
Sign up to set email alerts
|

Coastal cliff‐top ground motions as proxies for environmental processes

Abstract: [1] A two-year dataset of coastal cliff microseismic ground motions is used to explore energy transfer to a cliff. The long-term dataset enables us to characterise cliff motion responses to a wide range of environmental processes and examine whether short-term characteristics are representative of the long-term. We examine whether cliff-top motions are reliable proxies for environmental processes to inform future investigations into the drivers of erosion. The study is based at an actively eroding, macrotidal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 65 publications
0
28
0
Order By: Relevance
“…Previous studies have demonstrated that high-frequency cliff shaking, with the frequency range varying slightly between study locations, produces higher correlation coefficients with modelled and measured cliff toe wave conditions than microseism (MS) and long-period (LP) frequencies that represent wave loading in the nearshore and offshore (Norman et al, 2013, Vann Jones et al, 2015Young et al, 2016). HT ground motion signals have also produced higher correlation coefficients with observed rockfall (Vann Jones et al, 2015).…”
Section: Field Datamentioning
confidence: 98%
See 4 more Smart Citations
“…Previous studies have demonstrated that high-frequency cliff shaking, with the frequency range varying slightly between study locations, produces higher correlation coefficients with modelled and measured cliff toe wave conditions than microseism (MS) and long-period (LP) frequencies that represent wave loading in the nearshore and offshore (Norman et al, 2013, Vann Jones et al, 2015Young et al, 2016). HT ground motion signals have also produced higher correlation coefficients with observed rockfall (Vann Jones et al, 2015).…”
Section: Field Datamentioning
confidence: 98%
“…Wave model. In the absence of monitored cliff toe wave conditions, a linear wave model based on that of Battjes and Stive (1985) (see Norman et al, 2013) was used to transform wave heights measured at the wave buoy. Wave heights were transformed by shoaling and energy dissipation via turbulence as they break in decreasing water depths (calculated from the tide gauge time-series for the monitoring period) across the nearshore and foreshore profile normal to the cliff seaward of each seismometer ( Fig.…”
Section: Wave Datamentioning
confidence: 99%
See 3 more Smart Citations